Caracteristicas gerais e classificacao de solos basalticos da regiao Central do Estado de Sao Paulo. - Espindola, C. R.; Alonso, O. (My University, 1983)
Giving a special emphasis on soil classification relative to their positions in the landscape, five soil profiles in the Barra Bonita-Jau area were characterized through morphological, granulometric and chemical routine soil analysis. It was observed that the soil structure gradually changes from strong blocks with cutans (lowlands and smooth parts - Jau). In this direction, the silt/clay ratio and the base saturation is reduced, and the aluminium saturation increases. -from English summary
General characteristics and classification of basaltic soils in the central region of the state of Sao Paulo, Brazil